THE EFFECT OF SIMULTANEOUS COMPETITION EXERCISES WITH THE (CROSS FIT) ON THE PERFORMANCE ENDURANCE OF YOUNG SOCCER PLAYERS - Assist.Lecturer, Adnan Muhammad Shenawah; Assist. Prof. Dr. Abdulla Mohammed Tayawy (American Journals, 2023)
The study aimed to reveal the effect of competition training in conjunction with (CROSS FIT) exercises on the performance endurance of young football players, to identify the results of the pre and posttests, the performance endurance of young football players for the experimental and control research groups, and to compare the differences between the results of the two posttests, the performance endurance of the players. Youth football between the experimental and control groups.
Keywords: competition exercises, synchronized training, cross fit exercises, performance endurance, youth stage.